The Design of a Mechanized Onion Transplanter for Bangladesh with Functional Testing - Spencer Stubbs; Jonathan Colton (Agriculture, 2022)
Rising labor costs and the inefficient manual methods of cultivating red onions in Bangladesh contribute to the country’s failure to meet is own demand. Mechanizing the process of transplanting red onion seedlings will reduce the manual labor required while increasing crop yields. This paper provides an initial study of a proposed mechanized onion transplanter designed to attach to the back side of a two-wheel tractor with power tiller operated-seeder, commonly used in Bangladesh. Testing of a prototype made from these designs proves that the design is functional but requires further development for commercial/widespread use.